Heavy-ion induced quasi-elastic reactions in view of the NUMEN project. (1st March 2023) - Cavallaro, M; Agodi, C; Auerbach, N; Bellone, J I; Bijker, R; Brischetto, G A; Burrello, S; Calabrese, S; Cappuzzello, F; Carbone, D; Ciraldo, I; Colonna, M; et al.
Abstract: Double charge exchange (DCE) reactions induced by heavy ions and other direct reactions characterized by same projectile and target are crucial tools to access information relevant for neutrinoless double beta decay nuclear matrix elements. In this context the NUMEN project aims to investigate, for each system of interest, not only the DCE channel but also the whole set of reactions promoted by the same projectile/target interaction in the same experimental conditions and within the same theoretical framework. An example of the application of such a multi-channel approach is presented here.